Downregulation of Fat Mass and Obesity-Related Protein in the Anterior Cingulate Cortex Participates in Anxiety- and Depression-Like Behaviors Induced by Neuropathic Pain - Wang, Xiao-Ling; Wei, Xin; Yuan, Jing-Jing; Mao, Yuan-Yuan; Wang, Zhong-Yu; Xing, Na; Gu, Han-Wen; Lin, Cai-Hong; Wang, Wen-Ting; Zhang, Wei; Xing, Fei (Frontiers in Cellular Neuroscience, 2022)
RNA N6-methyladenosine (m6A) modification represents another layer of gene regulation. Fat mass and obesity-related protein (FTO) is the main N6-methyladenosine demethylase. FTO is involved in the occurrence and maintenance of neuropathic pain (NP). NP often induces mental disorders. We found that NP downregulated the expression of FTO in the anterior cingulate cortex (ACC), inhibited the expression of matrix metalloproteinase-9 (MMP-9) in the ACC, maladjusted the brain-derived neurotrophic factor precursor (proBDNF) and mature brain-derived neurotrophic factor (mBDNF) levels in the ACC, and induced anxiety- and depression-like behaviors in mice. Blocking the downregulation of FTO in the ACC induced by peripheral nerve injury could reverse the anxiety- and depression-like behaviors of mice. Contrarily, downregulation of simulated FTO induced anxiety- and depression-like behaviors in mice. After peripheral nerve injury, the binding of FTO to MMP-9 mRNA decreased and the enrichment of m6A on MMP-9 mRNA increased. In conclusion, downregulation of FTO in ACC contributes to the occurrence of anxiety- and depression-like behaviors in NP mice.